2022
DOI: 10.1002/jcp.30869
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial respiratory complexes: Significance in human mitochondrial disorders and cancers

Abstract: Mitochondria are pivotal organelles that govern cellular energy production through the oxidative phosphorylation system utilizing five respiratory complexes. In addition, mitochondria also contribute to various critical signaling pathways including apoptosis, damage-associated molecular patterns, calcium homeostasis, lipid, and amino acid biosynthesis. Among these diverse functions, the energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 297 publications
0
11
0
Order By: Relevance
“…The bioinformatics analysis revealed that the regulatory effect of METTL3 on the biological behavior of LPS-treated osteoclasts may be attributed to a mitochondrial dysfunction. Mitochondria are double-membrane organelles known as “energy generators” of the cells, converting nutrients and oxygen into ATP through oxidative phosphorylation [ 41 ]. As the master intracellular power producer, the proper function of mitochondria is critical for biological processes demanding energy, including cell survival, differentiation and activation [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bioinformatics analysis revealed that the regulatory effect of METTL3 on the biological behavior of LPS-treated osteoclasts may be attributed to a mitochondrial dysfunction. Mitochondria are double-membrane organelles known as “energy generators” of the cells, converting nutrients and oxygen into ATP through oxidative phosphorylation [ 41 ]. As the master intracellular power producer, the proper function of mitochondria is critical for biological processes demanding energy, including cell survival, differentiation and activation [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial OXPHOS system plays a significant role in maintaining the energy balance of aggressively growing tumors 20 . The MG encoded machinery, constitutes the critical components of this OXPHOS pathway to generate 90% of the cellular ATP 7 . In concert with the nDNA‐encoded multiple RC proteins, the MG thus plays a pivotal role in driving the OXPHOS pathway and fueling tumor growth and progression.…”
Section: Discussionmentioning
confidence: 99%
“…In the OXPHOS system, RCI serves as the entry gate for the electron transport system to begin 7 . Alterations in RCI may lead to higher ROS production through electron leaking and inhibition of intrinsic apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulated OXPHOS pathway is closely related to the process of EMT and tumor metastasis [ 43 ]. In a relatively nutrient deficient environment, the oxidative stress reaction promotes tumor cells to produce lactic acid and other metabolites through glycolysis, and further supply the anabolism of tumor cells with OXPHOS as the main metabolic pathway, to promote tumor growth [ 44 ].…”
Section: Mitochondrial Metabolismmentioning
confidence: 99%